2018
DOI: 10.1029/2018gl079309
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Hydroxymethane Sulfonate to Ambient Particulate Matter: A Potential Explanation for High Particulate Sulfur During Severe Winter Haze in Beijing

Abstract: PM2.5 during severe winter haze in Beijing, China, has reached levels as high as 880 μg/m3, with sulfur compounds contributing significantly to PM2.5 composition. This sulfur has been traditionally assumed to be sulfate, although atmospheric chemistry models are unable to account for such large sulfate enhancements under dim winter conditions. Using a 1‐D model, we show that well‐characterized but previously overlooked chemistry of aqueous‐phase HCHO and S(IV) in cloud droplets to form a S(IV)‐HCHO adduct, hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
122
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(130 citation statements)
references
References 87 publications
(131 reference statements)
4
122
0
Order By: Relevance
“…Similarly, AMS measurements may have identified HMS as sulfate as explained above. This is also consistent with the explanation provided by Moch at al. (2018) and Song at al.…”
Section: Resultssupporting
confidence: 94%
“…Similarly, AMS measurements may have identified HMS as sulfate as explained above. This is also consistent with the explanation provided by Moch at al. (2018) and Song at al.…”
Section: Resultssupporting
confidence: 94%
“…Increasing numbers of observations have revealed that anthropogenic emission-relevant aerosol species, such as sulfate, nitrate and ammonium (denoted as SNA), are the predominant inorganic species in the wintertime PM 2.5 in China (Y. S. Yang et al, 2015). Various reaction paths during haze events have also been proposed (e.g., Zheng et al, 2015;Cheng et al, 2016;Wang et al, 2016;Moch et al, 2018;Wang et al, 2018;Shao et al, 2019). For example, Moch et al (2018) used a 1-D model and revealed the importance of aqueousphase chemistry of HCHO and S(IV) in cloud droplets by forming a S(IV)-HCHO adduct, hydroxymethane sulfonate.…”
mentioning
confidence: 99%
“…Various reaction paths during haze events have also been proposed (e.g., Zheng et al, 2015;Cheng et al, 2016;Wang et al, 2016;Moch et al, 2018;Wang et al, 2018;Shao et al, 2019). For example, Moch et al (2018) used a 1-D model and revealed the importance of aqueousphase chemistry of HCHO and S(IV) in cloud droplets by forming a S(IV)-HCHO adduct, hydroxymethane sulfonate. Shao et al (2019) implemented four heterogeneous sulfate formation mechanisms (via H 2 O 2 , O 3 , NO 2 and transition metal ions on aerosols) into GEOS-Chem model, which partially reduced the modeled low bias in sulfate concentrations.…”
mentioning
confidence: 99%
“…The oxygen‐containing fragment ions, such as C 2 H 3 O + , C 14 H 7 O 2 + , C 3 H 7 O + , and C 11 H 14 O 5 + , and some oxygen‐containing unsaturated hydrocarbon ions even over m/z 200, such as C 16 H 14 O + , C 17 H 13 O 3 + , and C 22 H 18 O 4 + , may represent alcohols and carbonyl compounds in the atmosphere, which are mainly from automobile exhaust and atmospheric photochemical reactions . The nitrogen‐containing fragment ions and their oxidation derivatives in the atmosphere, such as C 2 H 7 N 3 + , C 2 H 2 N + , C 4 H 12 NO + , C 3 H 8 NO + , and C 5 H 12 N 2 O 3 + , which may be the heterocyclic compounds and the sulfur‐containing fragment ions and their oxidation derivatives, such as C 2 H 4 S 3 + , C 8 H 3 S + , and C 7 H 15 SO + , which may be the thiols and sulfonates are produced mainly by the burning of fossil fuels, biomass, and garbage, as well as vehicle emissions and, even, cooking, with secondary formation produced by landfill fermentation, organic solvent volatility, hydrocarbon oxidation, etc. In Table , unsaturated hydrocarbons ions, including C 16 H 10 + , C 20 H 12 + , and C 22 H 12 + , may be polycyclic aromatic hydrocarbons (PAHs) .…”
Section: Resultsmentioning
confidence: 99%